SPIRITUALITAS URBAN DALAM PENGALAMAN KEAGAMAAN DAN EKSPRESI ESTETIS SENIMAN MURAL - Sudarti, Dwi Okti (Smart Education, 2025)
Abstract: This study has important relevance in viewing mural art not merely as an aesthetic expression in urban spaces, but also as a medium that conveys messages of spirituality and religious experience. The main objective of this study is to reveal how urban spirituality contributes to the formation of the religious and cultural identity of mural artists in modern society, as well as how mural works function as a means of negotiation between religious identity and urban identity in artistic practice. This study uses a qualitative approach with a literature review method, based on Joachim Wach's thinking, which interprets religious experience as an inner relationship between humans and their minds with God. The results show that mural art in urban spaces not only serves as an aesthetic expression or social criticism, but also as a spiritual and cultural medium that reflects the religious dynamics of urban communities. Murals become a symbolic space where spiritual, moral, and social values interact through communicative visual language, while also marking a shift in religiosity from institutional forms to more personal and creative expressions. Thus, murals function as cultural da'wah that represent a dialogue between faith, culture, and modernity in the context of urban spirituality. The findings of this study confirm that every mural, even if it appears far from religious values, actually contains spiritual messages implied in its symbols, colours, and visual meanings.Keyword: aesthetic expression;mural artists;religious experience.Abstrak: Penelitian ini memiliki relevansi penting dalam melihat seni mural bukan sekadar sebagai ekspresi estetika di ruang perkotaan, tetapi juga sebagai medium yang memuat pesan spiritualitas dan pengalaman keagamaan. Tujuan utama penelitian ini adalah mengungkap bagaimana spiritualitas urban berkontribusi terhadap pembentukan identitas keagamaan dan kultural seniman mural dalam masyarakat modern, serta bagaimana karya mural berfungsi sebagai sarana negosiasi antara identitas religius dan identitas urban dalam praktik kesenian. Penelitian ini menggunakan pendekatan kualitatif dengan metode kajian kepustakaan (literature review), berlandaskan pemikiran Joachim Wach yang memaknai pengalaman keagamaan sebagai hubungan batiniah antara manusia dan pikirannya dengan Tuhan. Hasil penelitian menunjukkan bahwa seni mural di ruang urban tidak hanya berperan sebagai ekspresi estetis atau kritik sosial, tetapi juga sebagai medium spiritual dan kultural yang merefleksikan dinamika religiusitas masyarakat perkotaan. Mural menjadi ruang simbolik tempat nilai-nilai spiritual, moral, dan sosial berinteraksi melalui bahasa visual yang komunikatif, sekaligus menandai pergeseran religiusitas dari bentuk institusional menuju ekspresi yang lebih personal dan kreatif. Sehingga, mural berfungsi sebagai dakwah kultural yang merepresentasikan dialog antara iman, budaya, dan modernitas dalam konteks spiritualitas urban. Temuan penelitian ini menegaskan bahwa setiap karya mural, meskipun tampak jauh dari nilai-nilai religius, sesungguhnya mengandung pesan spiritual yang tersirat dalam simbol, warna, dan makna visualnya.Kata kunci: ekspresi estetis;pengalaman keagamaan;seniman mural.